2007
DOI: 10.1189/jlb.0107065
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CD28 expression on CD8+ T cells by CTLA-4

Abstract: CD28 and CTLA-4 are the critical costimulatory receptors that predominantly determine the outcome of T cell stimulation, with CD28 promoting positive costimulation and CTLA-4 inducing inhibitory signals. Blockage of the B7-CD28/CTLA-4 pathway leads to transplantation tolerance. However, the exact mechanism of the inhibitory function of CTLA-4 remains elusive. Here, we investigated the influence of CTLA-4 expression on CD28 using CTLA-4-transfected Jurkat T cells as well as primary T cells. Up-regulation of CTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 58 publications
2
16
1
Order By: Relevance
“…Consistent with earlier reports (12, 19 -21), we observed that Ag presentation in the presence of blocking Ab against CD86, but not CD80, resulted in significantly lower effector T cell proliferation than in controls. In addition, whereas selective costimulation by CD86 ϩ T cells results in down-regulation of CD28 expression on the surface upon activation (22). However, our observation that CD4 ϩ T cells costimulated preferentially by either CD80 or CD86, or both had comparable levels of CD28 and CTLA-4 on their surface (not shown).…”
Section: Discussioncontrasting
confidence: 52%
“…Consistent with earlier reports (12, 19 -21), we observed that Ag presentation in the presence of blocking Ab against CD86, but not CD80, resulted in significantly lower effector T cell proliferation than in controls. In addition, whereas selective costimulation by CD86 ϩ T cells results in down-regulation of CD28 expression on the surface upon activation (22). However, our observation that CD4 ϩ T cells costimulated preferentially by either CD80 or CD86, or both had comparable levels of CD28 and CTLA-4 on their surface (not shown).…”
Section: Discussioncontrasting
confidence: 52%
“…Observed CD28 downregulation in the ENU group indicates depressed immune status and poor T-cell activation and is evidenced in human cancers in other studies [17] but such downregulation in glioma and its reconstituted expression is being shown here for the first time. CD28 downregulation results from increased CTLA-4 expression [38]. This supports present observations where CTLA-4 expression was elevated in glioma conditions.…”
Section: Discussionsupporting
confidence: 82%
“…T11TS causes CD28 and CD80 upregulation and CTLA-4 downregulation. CD28 upregulation and CTLA-4 blockade leads to immuno-enhancement and abolishes glioma-induced immunesuppression [38,40]. Observed CTLA-4 suppression by T11TS therapy may aid alleviation of glioma-induced immunesuppression and since CTLA-4 suppression is concurrent to CD28 upregulation, such alleviation in immune responses and of T-cell proliferation may occur through activation of the PI3K-Akt pathways to which the CD28-mediated costimulation is linked [41].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We did not measured CTLA-4 (cytotoxic T lymphocyte antigen-4), the homologous family member of CD28. CTLA-4 and CD28 take opposing effect in the activation and differention of T helper cells [40,41] and it is theoretically possible that antagonistic effects may have been induced without our knowledge (though we think this unlikely). Therefore, clinical trials are required to assess whether our observation translates into clinical outcomes related to survival or the immune response.…”
Section: Discussionmentioning
confidence: 97%